2012
DOI: 10.1007/s12291-011-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of Estrogen Receptor-α Gene & Metallothionein-1 Gene Polymorphisms in Type 2 Diabetic Women of Andhra Pradesh

Abstract: Type 2 diabetes mellitus (DM) is a multifactorial disease where both genetic and environmental factors contribute to its pathogenesis. Estrogen plays an important role in type 2 DM pathogenesis. A number of polymorphisms have been reported in the estrogen receptor (ESR1), including the XbaI and PvuII restriction enzyme polymorphisms of ESR1,which may be involved in disease pathogenesis. Metallothioneins (MT) act as potent antioxidants against various oxidative damages. Very few studies have indicated the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
(24 reference statements)
2
15
0
Order By: Relevance
“…The distribution of Pvu II and Xba I polymorphisms in our study showed an increased ratio of Pp to pp and that of Xx to xx genotypes and a reduced frequency of PP and XX genotypes of patients in comparison to that of Asian and Caucasian populations of European ancestry, even though African population showed a lower frequency of pp and xx genotypes [11,18-21]. As a matter of fact, linkage disequilibrium differential degree among different racial populations may explain previous contradiction among ERα gene polymorphism studies [22].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The distribution of Pvu II and Xba I polymorphisms in our study showed an increased ratio of Pp to pp and that of Xx to xx genotypes and a reduced frequency of PP and XX genotypes of patients in comparison to that of Asian and Caucasian populations of European ancestry, even though African population showed a lower frequency of pp and xx genotypes [11,18-21]. As a matter of fact, linkage disequilibrium differential degree among different racial populations may explain previous contradiction among ERα gene polymorphism studies [22].…”
Section: Discussionsupporting
confidence: 54%
“…Hallmarks of T2DM are insulin resistance in liver, skeletal muscle and fat, combined with insulin insufficiency owing to a slump in β-cell function [18]. Recognition of the susceptibility genes for T2DM may come to initial prevention of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our results reported that the ESR1 PvuII C and XbaI G allele 232 frequencies were similar to other studies among Arab population (El-Beshbishy et al 2015; 233 Motawi et al 2015). However, several studies showed distinct prevalence for these two 234 polymorphisms, particularly the XbaI alleles (Ganasyam et al 2012). Discrepancies in allelic 235 frequencies between reports may be attributed to the ethnic variability of the studied populations, 236 heterogeneity of the analyzed diseases and sample size.…”
supporting
confidence: 84%
“…These findings are supported by another observation on the association of some single‐nucleotide polymorphisms (SNPs) in MT genes, especially in the MT‐1A and MT2A locus, with diabetes and diabetic neuropathy in a Chinese population . By contrast, another polymorphism on MT1A gene (rs11076161) in the intron region has not been associated with increased susceptibility to DM2 in Indian women .…”
Section: Metallothionein and Diabetesmentioning
confidence: 71%